Elevated energy coupling and aerobic capacity improves exercise performance in endurance‐trained elderly subjects. Issue 4 (6th February 2013) - Conley, Kevin E.; Jubrias, Sharon A.; Cress, M. Elaine; Esselman, Peter C.
<x xml:space="preserve">Abstract</x> Increased maximal oxygen uptake (<inline-graphic xlink:href="ark:/27927/pgg3hkkkpk9" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />), mitochondrial capacity and energy coupling efficiency are reported after endurance training (ET) in adult subjects. Here we test whether leg exercise performance (power output of the legs, Pmax, at <inline-graphic xlink:href="ark:/27927/pgg3hkkkpmv" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) reflects these improvements with ET in the elderly. Fifteen male and female subjects were endurance trained for a 6 month programme, with 13 subjects (69.5 ± 1.2 years old, range 65–80 years old; n= 7 males; n= 6 females) completing the study. This training significantly improved Pmax (Δ17%; P= 0.003), <inline-graphic xlink:href="ark:/27927/pgg3hkkkpnd" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> (Δ5.4%; P= 0.021) and the increment in oxygen uptake (<inline-graphic xlink:href="ark:/27927/pgg3hkkkppz" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) above resting (<inline-graphic xlink:href="ark:/27927/pgg3hkkkpqh" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />; Δ9%; P < 0.02). In addition, evidence of improved energy coupling came from elevated leg power output per unit <inline-graphic xlink:href="ark:/27927/pgg3hkkkpr2" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> at the aerobic capacity [Δ(Pmax/<inline-graphic xlink:href="ark:/27927/pgg3hkkkpsm" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />); P= 0.02] and during submaximal exercise in the ramp test as measured by delta efficiency (ΔPex/Δ<inline-graphic xlink:href="ark:/27927/pgg3hkkkpt5" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />; P= 0.04). No change was found in blood lactate, muscle glycolysis or fibre type. The rise in Pmax paralleled the improvement in muscle oxidative phosphorylation capacity (ATPmax) in these subjects. In addition, the greater exercise energy coupling [Δ(Pmax/<inline-graphic xlink:href="ark:/27927/pgg3hkkkpvq" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) and delta efficiency] was accompanied by increased mitochondrial energy coupling as measured by elevated ATP production per unit mitochondrial content in these subjects. These results suggest that leg exercise performance benefits from elevations in energy coupling and oxidative phosphorylation capacity at both the whole‐body and muscle levels that accompany endurance training in the elderly.